Patients’ experiences of using an e-Health tool for self-management support after prostate cancer surgery: a deductive interview study explained through the FITT framework - Nilsson, Lina (BMJ Open, 2020)
OBJECTIVE: To evaluate patients’ experiences of using a web-based application, especially its usability as support for self-care activities after prostate cancer surgery. DESIGN: A deductive content analysis was used, stemming from the Fit between Individuals, Task and Technology (FITT) framework. SETTING: One surgical department in south of Sweden between October 2015 and April 2016 and between September 2017 and July 2018. PARTICIPANTS: Fifteen men who had undergone radical prostatectomy for prostate cancer. RESULTS: By organising data in accordance with the FITT model, three main categories with ten subcategories were identified. Patients gave feedback on functions that suited them and their needs, as well as potential adjustments and improvements. Patients experienced that ePATH gave them easy access to reliable information regarding their rehabilitation. Directed information about ePATH at enrolment was seen as important. ePATH was perceived to have a logical structure that was easy to follow. However, when the structure was unclear, patients became less motivated to use a function. CONCLUSIONS: Patients experienced ePATH as satisfactorily user-friendly and useful as a complementary self-management support after prostate cancer surgery, especially when the information and tasks were tailored to their preferences and the system design features supported individual autonomy.